Results from Phase I Clinical Trial with Intraspinal Injection of Neural Stem Cells in Amyotrophic Lateral Sclerosis: A Long‐Term Outcome. (18th May 2019) - Mazzini, Letizia; Gelati, Maurizio; Profico, Daniela Celeste; Sorarù, Gianni; Ferrari, Daniela; Copetti, Massimiliano; Muzi, Gianmarco; Ricciolini, Claudia; Carletti, Sandro; Giorgi, Cesare; Spera, Cristina; Frondizi, Domenico; et al.
Abstract: The main objective of this phase I trial was to assess the feasibility and safety of microtransplanting human neural stem cell (hNSC) lines into the spinal cord of patients with amyotrophic lateral sclerosis (ALS). Eighteen patients with a definite diagnosis of ALS received microinjections of hNSCs into the gray matter tracts of the lumbar or cervical spinal cord. Patients were monitored before and after transplantation by clinical, psychological, neuroradiological, and neurophysiological assessment. For up to 60 months after surgery, none of the patients manifested severe adverse effects or increased disease progression because of the treatment. Eleven patients died, and two underwent tracheotomy as a result of the natural history of the disease. We detected a transitory decrease in progression of ALS Functional Rating Scale Revised, starting within the first month after surgery and up to 4 months after transplantation. Our results show that transplantation of hNSC is a safe procedure that causes no major deleterious effects over the short or long term. This study is the first example of medical transplantation of a highly standardized cell drug product, which can be reproducibly and stably expanded ex vivo, comprising hNSC that are not immortalized, and are derived from the forebrain of the same two donors throughout this entire study as well as across future trials. Our experimental design provides benefits in terms of enhancing both intra‐ and interstudy reproducibility and homogeneity. Given the potential therapeutic effects of the hNSCs, our observations support undertaking future phase II clinical studies in which increased cell dosages are studied in larger cohorts of patients.Stem Cells Translational Medicine 2019;8:887&897 Abstract : In this manuscript we present data from a phase I clinical trial on 18 ALS patients treated with human neural stem cells. Treatment has been performed transplanting cells directly into anterior horn of spinal cord. Results suggested that the procedure is feasible, safe and induce a transitory decline of ALS‐FRS‐R score progression.